Analisis pengaruh corporate social responsibility dan corporate governance terhadap agresivitas pajak - Nur Hajijah, Evi; Septiyanti, Ratna; Agustina, Yenni (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of corporate social responsibility and corporate governance on tax aggressiveness. The dependent variable used in this study is tax aggressiveness. The independent variables in this study are corporate social responsibility, independent commissioners, institutional ownership, board of directors, and audit committee. The population in this study are manufacturing companies listed in Indonesian Stock Exchange in the year 2015-2020. The sampling method used in this research is purposive sampling method. Technical analysis of data using multiple linear regression analysis using SPSS 24 program. The results show that all independent variables have a positive effect in tax aggressiveness, meaning that the more disclosure of corporate social responsibility, the number of independent commissioners, institutional ownership, board of directors, and audit committee have no effect on tax aggressiveness.